Improvement of anal sphincter function before preventive stoma closure: modern options - O. Yu. Fomenko; S. I. Achkasov; A. Yu. Titov; D. V. Aleshin; A. I. Kalashnikova; S. V. Belousova; D. V. Yegorova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To investigate options of improvement of anal sphincter function of defunctioning loop by BFT and tibial nerve stimulation.Material and methods. Overall 23 patients with preventive stoma were included in original investigation. Diagnostic profilometry and sphincterometry were carried out. Treatment included BFT and tibial nerve stimulation for 10 days. Results. After treatment profilometry revealed statistically significant increase of mean resting pressure, while sphincterometry — at conation as well.Conclusions. Muscular structures of the defunctioning anal sphincter respond to BFT and tibial nerve stimulation, increasing both tension and force of voluntary contractions.